Reorganizing parasitic Delesseriaceae: taxonomic revision of Asterocolax - Freese, Jillian M.; Lane, Christopher E. (Phytotaxa, 2021)
Red algal parasites are highly host specific organisms that are morphologically reduced with decreased pigmentation. Only found within the Florideophyceae, red algal parasites have evolved within eight orders, with the greatest parasite diversity found in the Ceramiales. A quarter of the ceramialian parasites in the family Delesseriaceae are described in the genus Asterocolax. The initial morphological description of Asterocolax led to the creation of an independent genus devoted to these parasitic species, but molecular data have repeatedly demonstrated that Asterocolax species, and likely many other red algal parasites, resolve within the genera of free-living red algae, often within the same genus as their hosts. Here and in previous studies, phylogenetic analysis of the internal transcribed spacer region of the ribosomal DNA has shown at least six instances of independent evolution of Asterocolax species, mainly interspersed among the free-living macroalgal genera of Phycodrys and Polyneura. As most Asterocolax are sister species to their hosts, they are independently derived from a photosynthetic ancestor, and together, do not form a monophyletic parasitic genus. Here we conduct a long overdue taxonomic revision of the red algal parasitic genus Asterocolax, describe a new species within the genus, and propose nomenclatural changes for four other species to reduce the polyphyletic clades encompassing Asterocolax.